Preparedness for hospital practice in assuring quality of care - Abd. Manaf, Noor Hazilah; Dato Mohd Ghazali, Roslan Johari; Mohd Borhan, Nor Filzatun; Omar, Azura; Mohd, Dinon; Adewale, Abideen Adeyemi; Ismail, Izhairi; Abdul Hamid, Zabeda (Emerald Group Publishing Ltd., 2016)
Purpose: The purpose of this paper is to identify the dimensions of preparedness for hospital practice among newly graduated medical officers in Malaysian hospitals who are undergoing their housemanship training; and to compare the level of preparedness among the different curricula and predict the dimensions of preparedness for hospital practice. Design/methodology: A national study was carried out and data collection was by means of self-administered questionnaire. Data obtained (N=1213) were subjected to exploratory factor analysis (EFA) using SPSS version 18 in extracting the dimensions of preparedness for hospital practice. Findings: Nine dimensions of hospital practice were identified which were access to information and IT skills, interpersonal skills, basic skills and continuing professional development, holistic skills, coping skills, ethic and legal skills, patient management skills, scientific knowledge, and clinical skills. Overall, the respondents felt their medical schools prepared them for hospital practice. The strongest predictor for preparedness for hospital practice is coping skills. Holistic skill and preparedness for hospital practice was found to be negatively associated. Those who graduated from twining programmes between Malaysian and overseas universities were found to be better prepared for hospital practice. Social implications: An understanding on preparedness for hospital practice among newly graduated medical officers is a step forward in assuring patient safety and quality of care.